THE EFFECT OF KANGAROO COUNSELLING CARE METHOD TOWARDS ANTHROPOMETRY OF LOW-BIRTH-WEIGHT - Putri Saudia, Baiq Eka; Yulinda, Dwi (International Journal of Psychosocial Rehabilitation, 2021)
Objective: The result of population inter-census survey in 2015 revealed that Infants Mortality Rate reached 22.23 per 1000 of live birth, and one of its causes in Indonesia is BBLR by 10.2%. Moreover, the case of BBLR in Hospital Patut Patuh Patju of West Lombok Regency in 2017 was 16.25% slightly decreased than in 2016 by 17.11%. One of the BBLR’s care efforts which is proven simple, cheap, and highly recommended is Kangaroo Mother Care (KMC). This study aimed at finding out the effect of Kangaroo Counselling Care Method towards the increase of baby’s body length for low birth weight at Hospital Patut Patuh Patju of West Lombok Regency. Method: This study used Quasi Experimental under Nonequivalent Control Group Design with 34 babies as sample who were divided into two groups; intervention group consisted of 19 babies treated through counselling, and Kangaroo Care Method, meanwhile, the control group was 15 babies treated through everyday Baby Care. Result: The increase of babies’ body length in intervention group was 1.29 cm. Meanwhile, the control group was 1.01 cm per 2 weeks. The result of statistical test using Mann Whitney was p = 0,005. Conclusion: There is an effect of Kangaroo Counselling Care Method towards the increase of babies’ body length for low birth weight at Hospital Patut Patuh Patju of West Lombok Regency.